2014
DOI: 10.2807/1560-7917.es2014.19.19.20800
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor: Measles on the cruise ship: links with virus spreading into an emergency department in Southern Italy

Abstract: Recently, Lanini et al. described an outbreak of measles that occurred on a ship cruising the western Mediterranean Sea, involving 27 cases among crew members and passengers between 20 February and 1 March 2014 [1]. Cases originated from different countries, six were from Italy. As highlighted by the authors, at the time of their preliminary report, the number of cases among passengers was likely to be underestimated, given that the incubation time for measles ranges from seven to 18 days, and the mean passeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…We thank Cozza et al for their letter in response to our paper [1]. The letter is a timely report and a good opportunity to provide additional information about the outbreak and share some general considerations.…”
Section: Lettersmentioning
confidence: 91%
See 2 more Smart Citations
“…We thank Cozza et al for their letter in response to our paper [1]. The letter is a timely report and a good opportunity to provide additional information about the outbreak and share some general considerations.…”
Section: Lettersmentioning
confidence: 91%
“…Seven of the 29 confirmed cases developed symptoms at home after returning from the cruise. These cases included a young child (passenger) from Lazio, a young child (passenger) from Umbria, an adult passenger from Sardinia who needed admission to an intensive care unit, two cases from Lecce (an adult passenger and a crew member), an adult passenger from Bari, and the teenage passenger from Brindisi reported by Cozza et al [1].…”
Section: Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 56 cases include 28 primary cases (crew and passengers) and 28 secondary cases; 39 of 56 case-patients were Italian and 17 were of foreign origin. One other secondary outbreak linked to the cruise ship has been reported ( 2 ). …”
Section: The Studymentioning
confidence: 99%
“…Measles virus genotype B3 was identified in 7 cases, and phylogenetic analysis showed that viral sequences were identical to each other and to those obtained from the cruise ship outbreak ( 2 , 4 ) (measles nucleotide surveillance [MeaNS] database accession nos. 62563, 62564, 67009, 67016, 62565, 67017, and 67020).…”
Section: The Studymentioning
confidence: 99%